Cassini/RPWS/HFR LESIA/Kronos QTN Data Collection V1.0 - Schippers, Patricia; Moncuquet, Michel; Cecconi, Baptiste (PADC, 2013)
This collection is composed of Cassini RPWS Quasi Thermal Noise (QTN) data set contains thermal plasma parameters derived by QTN spectroscopy analysis applied on data acquired with the High Frequency Receiver (HFR) during the perikrones of the entire mission.